The ontogeny of memory persistence and specificity - Ramsaran, Adam I. (Dev Cogn Neurosci, 2018)
Interest in the ontogeny of memory blossomed in the twentieth century following the initial observations that memories from infancy and early childhood are rapidly forgotten. The intense exploration of infantile amnesia in subsequent years has led to a thorough characterization of its psychological determinants, although the neurobiology of memory persistence has long remained elusive. By contrast, other phenomena in the ontogeny of memory like infantile generalization have received relatively less attention. Despite strong evidence for reduced memory specificity during ontogeny, infantile generalization is poorly understood from psychological and neurobiological perspectives. In this review, we examine the ontogeny of memory persistence and specificity in humans and nonhuman animals at the levels of behavior and the brain. To this end, we first describe the behavioral phenotypes associated with each phenomenon. Looking into the brain, we then discuss neurobiological mechanisms in the hippocampus that contribute to the ontogeny of memory. Hippocampal neurogenesis and critical period mechanisms have recently been discovered to underlie amnesia during early development, and at the same time, we speculate that similar processes may contribute to the early bias towards memory generalization.